Learning PostgreSQL : create, develop, and manage relational databases in real-world applications using PostgreSQL /: create, develop, and manage relational databases in real-world applications using PostgreSQL. (2015) - Juba, Salahaldin; Volkov, Andrey; Vannahme, Achim
No abstract available